1989
DOI: 10.1103/physrevlett.62.870
|View full text |Cite
|
Sign up to set email alerts
|

Pb(n, nx)at 65 MeV and the Isospin Structure of the Giant Quadrupole Resonance Region

Abstract: The first Pb(A2,«'x) data (at 65 MeV) are compared to earlier (61-66 MeV) (p,p'x) data. The isovector sensitivity of these nucleon probes is used to determine M"/M p -N/Z -1.54 for the giant quadrupole resonance (GQR). This result is consistent with other direct GQR measurements, 2i + data connected through core polarization, and several microscopic random-phase-approximation calculations, but in disagreement with a K~'/n + study which gives M"/M p =3.8 ± 1.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The present results for Pb have been compared to other RPA calculations in Ref. [28], and are shown there as entry d of Table I. A different pairing force producing relatively smaller gaps was also used to test the sensitivity; the results were qualitatively the same.…”
Section: State Inmentioning
confidence: 79%
See 1 more Smart Citation
“…The present results for Pb have been compared to other RPA calculations in Ref. [28], and are shown there as entry d of Table I. A different pairing force producing relatively smaller gaps was also used to test the sensitivity; the results were qualitatively the same.…”
Section: State Inmentioning
confidence: 79%
“…This is a common problem in all the RPA calculations of Ref. [28] and in other similar calculations [29 -31]. In the quasiparticle RPA model of Pomar, Blomqvist, Liotta, and Insolia [31], in which four-quasiparticle states were included, it was found that the first 2+ state of Pb could be reproduced by multiplying matrix elements involving the 1h9/2 and 2f7&~s hells by a factor of 1.95.…”
Section: State Inmentioning
confidence: 95%
“…A comparison of m+ and m inelastic scattering allows an isospin separation of nuclear transitions into contribu- lying levels in lighter nuclei, the Pb giant resonance value for M"/M& is not in agreement with that from neutron and proton scattering; for those probes the extracted value of M"/M is closer to the N/Z expectation of the collective model [8,9].…”
Section: Introductionmentioning
confidence: 77%
“…One of the reactions where very little data have been reported is the (n,n'x) reaction at intermediate energies. Only one experiment above 30 MeV has been published, reporting data at 65 MeV from University of California on iron, tin and lead targets [8,9].…”
Section: Introductionmentioning
confidence: 99%